Structure determination and activity manipulation of the turfgrass ABA receptor FePYR1. Issue 1 (December 2017) - Ren, Zhizhong; Wang, Zhen; Zhou, X.; Shi, Huazhong; Hong, Yechun; Cao, Minjie; Chan, Zhulong; Liu, Xue; Xu, H.; Zhu, Jian-Kang
Abstract Turfgrass are widely cultivated ornamental plants that have important ecological, societal and economical values. However, many turfgrass species are susceptible to drought and demand frequent irrigation thus consuming large amounts of water. With the ultimate goal of improving drought resistance in turfgrass, we identified several ABA receptors in turfgrass that are important to mediate ABA signaling and drought stress response. The ABA receptor FePYR1 from turfgrassFestuca elata was demonstrated to bind ABA as a monomer. Crystal structure analysis revealed that FePYR1 recognizes and binds ABA by the common gate-latch-lock mechanism resembling the Arabidopsis ABA receptors, but the ABA binding pocket in FePYR1 shows discrepant residues resulting in different binding affinity to ABA. Structure-guided alterations of amino acid residues in FePYR1 generated ABA receptor variants with significantly increased ABA binding affinity. Expression of FePYR1 in Arabidopsis conferred enhanced drought resistance in the transgenic plants. These findings provided detailed information about FePYR1 and demonstrated that structure-assisted engineering could create superior ABA receptors for improving plant drought resistance. The detailed structural information of FePYR1 would also assist future rational design of small molecules targeting specific ABA receptors in economically important plant species.